Avatares de un manuscrito: las ciencias auxiliares de la Historia del Arte - Carvajal González, Helena (Anales de Historia del Arte, 2010)
The paper considers in what way Art History’s auxiliary disciplines, such as codicology, palaeography, and bibliography, among others, can contribute to art-historical research. Through consideration of Rodrigo Jimenez de Rada’s Breviarium Historiae Catholicae, held in the Biblioteca Historica Marques de Valdecilla, in addition to specific references to other illuminated manuscripts in the Complutense’s collections, the paper shows how these disciplines can offer corrections or refinements in areas such as dating and examining interrelationships among different works of art.